Description of Students' Mathematical Critical Thinking Ability on Circle Material in Class VIII of SMP Negeri 09 Lebong - Ristontowi Ristontowi; Sakut Adepio; Winda Ramadianti; Masri Masri; Rahmat Jumri (MASI Mandiri Edukasi, 2025)
Mathematical critical thinking ability is the capacity to investigate, discover, connect, and assess every aspect of a problem carefully and thoughtfully to arrive at the best solution. This study aims to describe students' mathematical critical thinking abilities regarding circles in Grade VIII at SMP Negeri 09 Lebong. This research is a qualitative descriptive study with 20 student participants. Three students were interviewed: one with high ability, one with medium ability, and one with low ability. Data collection methods included tests, interviews, and documentation. The research instruments consisted of test items and interview guidelines. The data analysis technique involved data collection, data reduction, data presentation, and conclusion. The results of the study show that high-ability students met all indicators of mathematical critical thinking: Interpretation, Analysis, Evaluation, and Conclusion. Medium-ability students met two indicators: Interpretation and Analysis. Low-ability students were unable to meet the indicators of mathematical critical thinking: Interpretation, Analysis, Evaluation, and Conclusion.